Intervención optométrica en paciente femenino de 22 años de edad, con albinismo atendido en Laboratorio Optométrico de la UTB. - Zambrano Boza, Naydelin Dayanna (2025)
The purpose of this clinical case study is to determine the refractive error of the 22-year-old female patient diagnosed with Albinism. Through a personalized eye exam, we seek to analyze the visual problems that affect your visual ability to carry out your daily activities normally. Compound myopic astigmatism is one of the main causes that explain why your visual acuity is not normal and because the cylinder has been hypercorrected, this causes your sensitivity to light to worsen. Due to this refractive problem, a measurement variation was carried out where his treatment will help his photophobia go down a little. The corrective lens with its proper protection seeks to reduce the patient's visual fatigue and help her carry out her daily activities and protect her eyes from the light of electronic devices, which is where she is most in direct contact. Results: An adjustment was made to his current lens prescription, modifying the cylinder with the goal of improving his visual acuity and light sensitivity. Conclusion: With the use of the new measurements in monofocal corrective lenses, the patient's visual acuity improved where she gradually adapted to her prescription without the need to make additional adjustments.